Potent antimyeloma activity of the novel bromodomain inhibitors I-BET151 and I-BET762 - Chaidos, A; Caputo, V; Gouvedenou, K; Liu, B; Marigo, I; Chaudhry, M; Rotolo, A; Tough, DF; Smithers, NN; Bassil, AK; Chapman, TD; Harker, NR; et al. (American Society of Hematology, 2014)
The bromodomain and extraterminal (BET) protein BRD2-4 inhibitors hold therapeutic promise in preclinical models of hematologic malignancies. However, translation of these data to molecules suitable for clinical development has yet to be accomplished. Herein we expand the mechanistic understanding of BET inhibitors in multiple myeloma by using the chemical probe molecule I-BET151. I-BET151 induces apoptosis and exerts strong antiproliferative effect in vitro and in vivo. This is associated with contrasting effects on oncogenic MYC and HEXIM1, an inhibitor of the transcriptional activator P-TEFb. I-BET151 causes transcriptional repression of MYC and MYC-dependent programs by abrogating recruitment to the chromatin of the P-TEFb component CDK9 in a BRD2-4–dependent manner. In contrast, transcriptional upregulation of HEXIM1 is BRD2-4 independent. Finally, preclinical studies show that I-BET762 has a favorable pharmacologic profile as an oral agent and that it inhibits myeloma cell proliferation, resulting in survival advantage in a systemic myeloma xenograft model. These data provide a strong rationale for extending the clinical testing of the novel antimyeloma agent I-BET762 and reveal insights into biologic pathways required for myeloma cell proliferation.